Prospective Studies Exploring the Possible Impact of an ID3 Polymorphism on Changes in Obesity Measures. Issue 4 (14th February 2018) - Svendstrup, Mathilde; Appel, Emil V.R.; Sandholt, Camilla H.; Ahluwalia, Tarunveer S.; Ängquist, Lars H.; Thuesen, Betina H.; Jørgensen, Marit E.; Pedersen, Oluf; Grarup, Niels; Hansen, Torben; Sørensen, Thorkild I.A.; Vestergaard, Henrik
Abstract : Objective: Changes in fat mass depend on adipogenesis and angiogenesis, mechanisms regulated by the inhibitor of differentiation‐3 (ID3). Id3 knockout mice showed attenuated increases in BMI and visceral fat mass. We hypothesized that the ID3 missense variant (rs11574‐A) would lead to an attenuated increase over time in fat mass, BMI, waist circumference (WC), and waist‐hip ratio (WHR) in humans. Methods: The genotyped study populations included the Obesity Research Group – Genetics (ORGGEN) cohort, a cohort of men with obesity ( N =  716) and of randomly selected men ( N  = 826) from the Danish draft register who were examined at mean ages of 20 and 46 years, and the Inter99 ( N  = 6, 116) and Health2006 ( N  = 2, 761) cohorts, two population‐based samples of middle‐aged people, followed up after 5 years. Results: In meta‐analyses of all data, no association was found between rs11574‐A and changes in BMI, WC, WHR, or fat mass. We found an association between rs11574‐A and cross‐sectional BMI ( N  = 10, 359, β: −0.16 kg/m 2 per allele, 95% CI: −0.30 to −0.01, P  = 0.033) and fat mass ( N  = 4, 188, β: −0.52 kg/m 2 per allele, 95% CI: −1.03 to −0.01, P  = 0.046). Conclusions: No consistent impact of the genetic variant on changes in fat mass, BMI, or fat distribution was found in three Danish cohorts.